Taking the bait: interrogation questions about hypothetical evidence may inflate perceptions of guilt - Crozier, William E. (Psychology, crime & law, 2020)
During suspect interviews, police will sometimes ask about hypothetical incriminating evidence to evoke a cue to deception - a technique known as a bait question. Previous research has demonstrated such questions can distort peoples’ memory for what evidence exists in a case. Here, we investigate whether such memory distortion can also cause people to see the suspect as more likely to be guilty. Across three experiments, we find exposure to bait questions led to participants hold inflated views of a suspect’s guilt. Further, we demonstrate bait questions cause reliable, robust memory distortion, leading participants to believe non-existent, incriminating evidence exists. However, we found no evidence to support the speculated mechanisms for this inflation - namely, (1) that source monitoring errors could lead people to misremember false evidence as real evidence and (2) that bait questions provide ‘key evidence’ to fill in the gaps of an incomplete theory of a case. In sum, bait questions have the problematic potential to shift jurors towards guilty verdicts. We suggest future research directions on bait questions, including the need for different designs to clarify why bait questions inflate guilt, and recommend practitioners avoid the use of bait questions.